Cultural differences in shame and guilt between American and Chinese preschoolers - Zhang, Dongying, author; Barrett, Karen Caplovitz, advisor; Lunkenheimer, Erika S., committee member; Morgan, George A., committee member (Colorado State University. Libraries, 2011)
The emotions of guilt and shame play a significant role in socialization. Many cross-national studies about shame in American and Chinese cultures use college students as their subjects. Little attention has been given to the investigation of differences in shame behaviors between American and Chinese young children, and even less to differences in guilt behaviors between these two populations. The purpose of this study was to gain a better understanding of similarities and differences in shame and guilt of preschoolers in these two countries. In this study, we hypothesized that children raised in Chinese families would show higher levels of shame-related behavior than those raised in American families; and that in both Chinese and American cultures, girls would show higher levels of shame-related behavior than boys. No directional predictions regarding guilt were made given the paucity of empirical literature on this topic. Thirty two three to three and a half-year-old children from the United States and thirty four children from China participated in this study. Results indicated that there were cross-national differences in both observed and parentally reported shame behaviors and in parentally reported guilt behaviors between Chinese and American samples, but no evidence of gender effects.
Keywords: education; social sciences